GLP-1 receptor agonist therapy and pregnancy: Evolving and emerging evidence - Maria S Varughese; Fidelma O'Mahony; Lakshminarayanan Varadhan (Clinical Medicine)
The prevalence of type 2 diabetes mellitus (T2DM) and obesity is increasing in young adults, posing significant risks around pregnancy. Obesity also impacts on fertility and the co-existence of polycystic ovarian syndrome increases the prevalence of cardiovascular metabolic risk factors. There has been a renewed interest in glucagon-like peptide-1 receptor agonists (GLP-1RA) in this context, due to their multi-dimensional impact on the reproductive axis, as well as their ability to simultaneously target weight loss and glycaemic control. There is, however, limited availability of safety data with respect to these newer non-insulin-based diabetes medications from the perspective of fetal development. As GLP-1RA are not licensed for use in pregnancy, with the increasing chances of incidental exposure from pre-conception use for obesity and T2DM, it is imperative that pre-conception counselling should be an integral part of consultation prior to the initiation of these drugs.